HUBUNGAN BEBAN KERJA DENGAN TINGKAT STRESS KERJA PERAWAT DALAM MENANGANI PASIEN COVID 19 DI RS HUSADA UTAMA SURABAYA - Dwi Astutik, Nurul; Rozi, Fahrur; Sholikhah, Dwi Uswatun (PRIMA WIYATA HEALTH, 2023)
The causes of stress that often occur in health workers include shift work, long working hours, ambiguous roles and role conflicts, and exposure of health workers to infection, one of which is the covid 19 virus which has an impact on stress by medical workers in the midst of the Covid-19 corona virus outbreak. 19 right now. This study aims to determine the relationship between workload and work stress levels of nurses in handling Covid 19 patients at Husada Utama Hospital in Surabaya. The design of this research is an analytic survey with a cross sectional approach. The research population was all nurses in the inpatient room with a sample of 26 nurses who were taken by random sampling. The results showed that most of the respondents had a heavy workload, namely 14 respondents (53.9%), while the work stress level of most respondents, namely 16 respondents (61.6%) experienced heavy work stress. The analysis statistic of the analysis test using the Spearman's rho statistical test showed that the P-value was 0.014 <0.05 and the direction of the relationship was positive 0.0321 so it can be concluded that there is a relationship between workload and work stress levels of nurses in handling Covid 19 patients at Husada Utama Hospital. Surabaya. The workload and work stress experienced by nurses in the COVID-19 room are quite heavy due to poor working conditions, work overload, high-risk work. If this workload problem is not handled, it is feared that the higher work stress will be experienced by the nurses in the COVID-19 room